2006
DOI: 10.1590/s0066-782x2006001500005
|View full text |Cite
|
Sign up to set email alerts
|

Análise da dispersão do intervalo QT em pacientes com infarto agudo do miocárdio: efeito da reperfusão coronariana

Abstract: The study shows that DeltaQT is significantly reduced in patients with acute myocardial infarction submitted to successful thrombolysis, and is increased in infarcted patients with closed artery. DeltaQT reduction between the pre- and post-thrombolysis condition was a predictor for coronary reperfusion of those patients, and did not show correlation to ventricular arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
(16 reference statements)
1
4
0
1
Order By: Relevance
“…Different studies have shown that cQTd is increased in the early phase of STEMI [19, 20] and that re-establishment of the infarct-related artery flow decreases it [10, 11, 21, 22]. In this sense, our data are in agreement with previous findings: the achievement of a TIMI flow grade 3 after PPCI significantly decreased cQTd.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Different studies have shown that cQTd is increased in the early phase of STEMI [19, 20] and that re-establishment of the infarct-related artery flow decreases it [10, 11, 21, 22]. In this sense, our data are in agreement with previous findings: the achievement of a TIMI flow grade 3 after PPCI significantly decreased cQTd.…”
Section: Discussionsupporting
confidence: 93%
“…However, the timing of cQTd evolution after coronary revascularization has not been widely studied. In earlier works, the decrease of cQTd was measured from 24 h [22] to 8 days [11]after artery opening. Our data show that this finding is evident as early on as 1 h after arterial recanalization.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in QTcD after fibrinolysis was predictive of coronary reperfusion. 13 There is evidence that recanalization after an acute event is associated with a decrease in QTcD, as observed in the TEAM-2 and TEAM-3 studies. 14 , 15 To our knowledge, there is no study on QTcD after PIS combined with angiographic perfusion imaging (TIMI flow and Blush grade) after tenecteplase (TNK) administration.…”
Section: Introductionmentioning
confidence: 84%
“…Lopes et al [ 21 ] studied the effect of thrombolytic therapy on QTD in patients with STEMI, and showed that QTD was significantly shorter in patients with STEMI who underwent successful thrombolysis (Table 5 ). On the other hand, they found that QTD did not correlate with ventricular arrhythmia; however, QTD was higher in patients with ventricular arrhythmia than those without.…”
Section: Discussionmentioning
confidence: 99%